Late stage differential exhumation of crustal blocks in the central Eastern Alps: Evidence from fission track and (U-Th)/He thermochronology - Wölfler, A.; Dekant, C.; Danišík, Martin; Kurz, W.; Dunkl, I.; Putiš, M.; Frisch, W. (Blackwell Publishing Ltd, 2008)
Thermal history modelling based on zircon- and apatite fission track and apatite (U–Th)/He data constrain and refine the near-surface exhumation of the south-eastern Tauern Window (Penninic units) and neighbouring Austroalpine basement units in the Eastern Alps. Fast exhumation on both sides of the Penninic/Austroalpine boundary coincides with a period of lateral extrusion and tectonic denudation of the Penninic units in Miocene time (22–12 Ma). The jump to older ages occurs within the Austroalpine unit along the Polinik fault, which therefore defines the boundary between the tectonically denuded units and the hangingwall at that time. According to the different (U–Th)/He ages between the Penninic Hochalm- and Sonnblick Domes we demonstrate a differential cooling history of these two domes in the latest Miocene and early Pliocene.